2012
DOI: 10.1111/j.1541-4337.2012.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Risk Assessment of Endocrine‐Disrupting Chemicals Derived from Plastic Food Containers

Abstract: In the manufacture of plastic containers, various materials such as additives (for example, plasticizers, stabilizers, antioxidants), polymers (for example, polystyrene [PS] for PC) presented in polymers, as additives (for example, phthalates for PVC) used in polymer manufacturing, and/or as contaminants from the polymers depending on physicochemical conditions such as temperature, UV light, pH, microwave, and mechanical stress. Some phthalates (for example, DEHP, DBP), styrene, or bisphenol have been suspecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(42 citation statements)
references
References 115 publications
0
42
0
Order By: Relevance
“…Phthalate esters are mainly used as plasticizers for Atmospheric Research 154 (2015) [138][139][140][141][142][143][144][145] improving the flexibility and workability of polymeric materials. Epidemiological, clinical, and experimental data have demonstrated that phthalates have a significant effect on male reproductive disorders, such as infertility, reduced sperm motility, and decreased sperm (Bang et al, 2012). The other chemical, bisphenol A, was first synthesized in 1891 (Dianin, 1891) and has been widely used since the 1950s in epoxy resins, polycarbonates, and other polymeric materials.…”
Section: Introductionmentioning
confidence: 98%
“…Phthalate esters are mainly used as plasticizers for Atmospheric Research 154 (2015) [138][139][140][141][142][143][144][145] improving the flexibility and workability of polymeric materials. Epidemiological, clinical, and experimental data have demonstrated that phthalates have a significant effect on male reproductive disorders, such as infertility, reduced sperm motility, and decreased sperm (Bang et al, 2012). The other chemical, bisphenol A, was first synthesized in 1891 (Dianin, 1891) and has been widely used since the 1950s in epoxy resins, polycarbonates, and other polymeric materials.…”
Section: Introductionmentioning
confidence: 98%
“…Approximately 140 million tons of different kinds of petroleum-derived synthetic plastics are produced every year and considerable amount of these plastics are introduced in the environment as industrial waste [3]. Unfortunately, it influences the endocrine system, impairs reproduction, or causes cancer [7]. However, these conventional plastics are resistant to microbial attack and end up in landfill burial sites for thousands of years causing shortage of landfill space and negative impact on wildlife through ingestion and entrapment [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…These compounds enhance process ability and improve the polymer properties both during processing and under the conditions of use. As a result of their various applications, there have been some concerns about the migration of additives when the polymer packaging is in contact with food [1,2]. The release of additives, initially present in the packaging, into product can cause undesirable flavors in the food or even promote toxicity and damage humans.…”
Section: Introductionmentioning
confidence: 99%